Features of Development of Socio-Communicative Competence in Primary Schoolchildren with Developmental Delays - Egorova M.A; Zarechnaya A.A.** (Moscow State University of Psychology and Education, 2019)
The paper presents outcomes of a study on the features of social and communicative competence in joint activities in children aged 7-8 years with developmental delays.In our study, the children displayed reduced ability to negotiate, to distribute actions, to adhere to the plan, to resolve conflicts.We outline the principles of designing the educational environment for children with developmental delays within comprehensive schools in accordance with the specifics of the children's socio-communicative competence and with a focus on the tasks set by the Federal State Education Standard of Primary Education for Students with Disabilities.Specially organised conditions as a system of specific measures ensuring the dynamics, integrity, technological effectiveness and productivity of socio-communicative competence development in children with developmental delays include the following: promoting development through a specially designed learning environment; arranging activities based on collaboration in pairs and small groups; monitoring, supporting and assessing communicative knowledge, skills and personal traits in children.